Effectiveness of Nutmeg Seed–Aloe Vera Ointment Compared with Ice Compresses for Bruise Healing: A Quasi-Experimental Study - Nur Hidayati; Ilma Fauziyah Firdaus; Aprelia Afidatul Hanafi (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Bruises are a common problem experienced by Tapak Suci athletes caused by impact or trauma that leads to bleeding under the skin, pain, and swelling. Despite their potential benefits, non-pharmacological therapies have not been widely chosen. This study aims to determine the effectiveness of giving Nutmeg seed and Aloe vera compared to ice compresses for bruises injuries recovery. A quasi-experiment design used on 46 Tapak Suci athletes who divided into two groups, and selected using accidental sampling technique. The intervention group was given Nutmeg seed and Aloe vera ointment for 7 days, and the control group was given ice compresses for 7 days. The instrument used was an observation sheet, and analyzed using Wilcoxon and Mann Whitney tests (α≤0.05). The study showed that 65.2% of respondents experienced fast healing after giving Nutmeg seed and Aloe vera. Both the intervention and control groups showed significant differences between pre-test and post-test results (p=0.001; p=0.000). There was a notable contrast in bruise coloration changes between the two groups during the pre-test and post-test assessments (p=1.000; p=0.001). In conclusion, Nutmeg seed and Aloe vera demonstrated greater efficacy in promoting bruise healing compared to ice compress therapy, accelerating recovery by approximately one day.